2009
DOI: 10.1002/pola.23781
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of doubly functionalized polar norbornenes by HPLC and their ruthenium‐catalyzed ring‐opening metathesis polymerization

Abstract: Doubly fuctionalized polar norbornenes bearing the cyano and ester groups in 2,3‐positions are synthesized and enantiomers are separated by high performance liquid chromatography (HPLC) with a chiral stationary phase. These optically active monomers are polymerized by ruthenium carbene catalysts, and high yields of the polymers were obtained. The chiral monomer bearing ethyl ester gave an optically active polymer of lower, but opposite sign of optical rotation (monomer [α]D = +61.0°, polymer [α]D = −3.1°). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Ru (G2) exhibited good activity with respect to the polymerization of NBDTPAC8, but the obtained polymer had an uncontrolled molecular weight and broad PDI due to slower initiation and faster propagation rates 56. It is widely known that Ru (G3) exhibits better control due to faster initiation and inhibits side reactions such as back‐biting 57. We found that Ru (G3) promoted higher activity than Ru (G1) and Ru (G2).…”
Section: Resultsmentioning
confidence: 83%
“…Ru (G2) exhibited good activity with respect to the polymerization of NBDTPAC8, but the obtained polymer had an uncontrolled molecular weight and broad PDI due to slower initiation and faster propagation rates 56. It is widely known that Ru (G3) exhibits better control due to faster initiation and inhibits side reactions such as back‐biting 57. We found that Ru (G3) promoted higher activity than Ru (G1) and Ru (G2).…”
Section: Resultsmentioning
confidence: 83%
“…52 It is widely known that Ru (G3) exhibits better control due to faster initiation and inhibits side reactions like back-biting. 53 Ru (G3) promoted higher activity than Ru (G1) and Ru (G2) initiators. In Table 1, the number-average molecular weights of poly(NBDTPA) obtained by Ru (G1), Ru (G2) and Ru (G3) were, respectively, 1.33, 3.52 and 3.91 Â 10 5 with yields of 20, 80 and 85%.…”
Section: Synthesis and Characterisationmentioning
confidence: 89%
“…However, when the amount of [Ru]-III catalyst was increased ([M]/[I] ratio = 200), the yield improved to 82% and a rather narrow polydispersity index of 1.05 was observed at −15 °C after 18 hours (entry 2, Table 1), indicating that corresponding polymer 1a was produced in a controlled living manner as has been reported by others. 3 f ,14 Therefore, this molar ratio (200) was adopted for the polymerization of the remaining monomers in Table 1.…”
Section: Resultsmentioning
confidence: 99%